Foliar Selenium Biofortification in Temperate Fruit Crops: Impact on Selenium Accumulation and Nutritional Quality of Fruits and Juices - Ján Mezey; Ivana Mezeyová; Adrián Selnekovič; Daniel Bajčan (Beverages)
As an essential mineral element, selenium (Se) must be consumed by organisms through food and beverages. A method used to raise the amount of Se in food made from plants is biofortification, which is the process that increases the bioactivity and content of Se in the edible parts of plants. Foliar fertilization is the most feasible method of introducing selenium into the food chain. The objective of this work was to determine the effect of foliar biofortification with Selenium on various quality attributes of fruit species suitable for fruit-based beverage production, with the main goal of verifying the incorporation of Se into plant tissues. During the growing season in 2023, sodium selenate was applied in an equivalent of 150 g/ha Se in professional raspberry, blueberry, redcurrant, honeysuckle and apple plantings, from which fruit-based juice was later produced and analyzed. There was significant increase (p ≤ 0.05) in the Se content in the fruit’s juice, which was the main goal. Furthermore, after the application of Se under the mentioned conditions, there was a significant (p ≤ 0.05) increase in nutritionally valuable parameters, such as antioxidant activity, ferulic acid and resveratrol, but also the content of glucose, fructose, malic acid, total acids, Mn, Ba, Ca, Li, myricetin and chlorogenic acid content. On the other hand, a decrease in some valuable indicators, but also heavy metals (Al, Cu, Cr), were noticed in some fruit juices.